Middle East Drugs Bazaar : Production, Prevention and Consumption - Robins, Philip (London Hurst & Company, 2016)
An in-depth look at illicit drugs and their social, political and economic impact across ten countries in the Middle East.
Include Index, Bibliography and Notex
Keywords: Middle East -- Drug abuse -- Drug traffic